IMPROVING THE ENGLISH SPEAKING TEACHING AND LEARNING PROCESS BY USING PROBLEM-BASED LEARNING AT PESANTREN’S MADRASAH - Al-Khusain, Abu Ali; Priyana, Joko (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This action research was aimed at improving the speaking teaching and learning process by using problem-based learning. The subjects were 27 students of grade XI of M adrasah A liyah Ali Maksum Pondok Pesantren Krapyak Yogyakarta . The data were collected using questionnaire, observation, and tests and were analysed descriptively and quantitatively. Problems that effectively improved the speaking teaching and learning process are real life problems based on the students’ experience and knowledge such as choosing Islamic school with boarding school system or State school. The findings show that problem-based learning improved teaching and learning process of speaking. They became actively participated in group discussion to overcome problems. The students were confident to speak English. The improvement of students’ speaking skill was proven by the increase of the test results. The students’ average score in the pre-test was 65, while in cycle one was 71 and 82 in cycle two.